(untitled) (REMUNOM, 2024)
Objective: To evaluate the acute effect of aerobic exercise on blood pressure and heart rate in hypertensive elderly people. Method: This is a quasi-experimental study, consisting of 10 elderly people from an extension project at a University Center who performed a gymnastics training session. Statistical analysis was performed using SPSS, version 23. To compare pre- and post-training results, the paired t-test was used, with a significance level of α = 0.05. Results: When comparing the values from pre to post moments, systolic blood pressure showed a significant result (p<0.001) with a percentage delta reduction of 18%. Conclusion: A gym training session reduces systolic blood pressure.